CHARCATERIZATION AND GROWTH KINETICS OF Phomopsis psidii CAUSING STYLER END ROT OF GUAVA (Psidium guava) (Applied Biological Research, 2025)
Styler end rot is one of the most significant diseases affecting the styler end of guava fruit, causing direct yield losses. The present study aimed to characterize the causal pathogen of styler end rot, Phomopsis psidii, on a physiological basis and to assess its growth kinetics (ΔrAUKC) under laboratory conditions. The effects of different nutrient media, temperature regimes, pH levels, carbon sources, nitrogen sources, and trace elements on fungal growth were evaluated. Among six nutrient media tested, potato dextrose agar (PDA) supported the highest diametric growth (90 mm) and growth rate (0.59 mm h⁻¹), producing white mycelium with a ring pattern. Maximum diametric growth (90 mm) and higher growth rates (0.56–0.59 mm h⁻¹) were observed at 25°C and pH 6.5 after 144 hours of incubation. Peak fungal growth occurred between 48 and 72 hours of incubation, irrespective of nutrient media, temperature, or pH. In terms of biomass production, starch was the most effective carbon source (1141.87 mg), potassium nitrate was the best nitrogen source (282.30 mg), and magnesium sulphate proved to be the most effective trace element (858.33 mg). Understanding the optimal growth conditions of Phomopsis psidii provides a foundation for developing targeted cultural and chemical management strategies against guava styler end rot.
Keywords: Fungal biomass; growth kinetics; guava; styler end rot; Phomopsis psidii; physiological studies